GP176 Morphological features of chronic gastritis associated with epstein-barr virus in children. (June 2019) - Novikova, Valeria; Gurina, Olga; Varlamova, Olga; Blinov, Aleksey; Hakizimana, Jean-Claude; Karpeeva, Yulia; Petrovsky, Andrey
Abstract : Introduction: The Epstein-Barr virus has been recently considered as an etiological cause of chronic gastritis. Objectives: To study the relationship between the morphological features of chronic gastritis and Epstein-Barr virus infection. Methods: 50 children (mean age 12.4 ± 0.3 years) with morphologically verified chronic gastritis were examined. In All patients, fibrogastroduodenoscopy was carried out and two biopsy samples from the body and antrum parts of the stomach were taken. Morphological assessment of biopsy specimens was done according to a standard visual analogue scale. The EBV was determined by immunohistochemical method. The EBV antibodies anti-EA IgG and anti-EBNA IgM were determined by ELISA using standard sets manufactured by 'Vector Best' company. Statistical processing of research materials was carried out using software and package Statistica for Windows (version 6.0). Results: Anti-EA IgG to EBV, indicating active virus replication, were identified in 36 children (72%). Antibodies to EBV class IgG M, characteristic of the acute stage of EBV infection, had not been found in any child. EBV was detected in 71.4% of biopsy specimens from the stomach of the children who had been tested anti-EA IgG positive. The presence of EBV antigens in the gastric epithelium revealed significant correlation with the presence of hemorrhages in the body of the stomach (r=0.68; p<0.05) and in the antrum (r=0.66; p<0.05), microthrombosis in the body of the stomach (r=0.38; p<0.05) and in the antrum (r=0.42; p<0.05), regenerative changes in the cervical epithelium of the gastric mucosa (r=0.32; p<0.05), fibrosis in the mucosa of the body of the stomach (r=0.46; p<0.05), atrophy of the glands of the body of the stomach (r=0.65; p<0.05), atrophy of antral glands (r=0.52; p<0.05), pylorization of fundal glands (r=0.5; p<0.05), hyperplasia of parietal cells (r=0.62; p<0.05), erosion in the body of the stomach (r=0.47; p<0.05), erosion in the antrum (r=0.36; p<0.05). Conclusions: Studies showed that in children with chronic gastritis, Epstein-Barr virus markers are detected in the blood with high frequency. There is a relationship between the presence of the Epstein-Barr virus in the gastric mucosa and histological signs of gastritis.